John Crowe Ransom - American Writers 18 : University of Minnesota Pamphlets on American Writers - Stewart, John L. (John Lincoln) (Book collections on Project MUSE., 1962)
John Crowe Ransom was one of the leading poets of his generation. A highly respected teacher and critic, Ransom was intimately connected to the early twentieth-century literary movement known as the Fugitives, later the Southern Agrarians. Around the year 1915, a group of fifteen or so Vanderbilt University teachers and students began meeting informally to discuss trends in American life and literature. Led by John Crowe Ransom, then a member of the university's English faculty, these young "Fugitives," as they called themselves, opposed both the traditional sentimentality of Southern writing and the increasingly frantic pace of life as the turbulent war years gave way to the Roaring Twenties. They recorded their concerns in a magazine of verse entitled the Fugitive, which, though it appeared little more than a dozen times after the first issue was published in 1922, proved to be in the vanguard of a new literary movement -- Agrarianism and a new way of analyzing works of art -- the New Criticism. As one of the group's major spokesmen (along with fellow members Allen Tate, Robert Penn Warren, and Donald Davidson), John Crowe Ransom eventually came to be known as the dean of twentieth-century American poets and critics.